2016
DOI: 10.1080/11287462.2016.1212608
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of resource habitat taboos and human health outcomes in the context of global environmental change

Abstract: The dependence of humans on the ecosystem services that natural resources provide is absolute. The need for social taboos as frameworks for governing natural resource abstraction is gaining widespread recognition especially within the context of climate change. However, the complex relationship between resource and habitat taboos (RHTs) and human health is not entirely understood. We conducted a systematic review of existing studies of the association between RHTs and human health outcomes, focusing on the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…While the present work shows that appeals to gods and spirits point to threats to coordination and cooperation in the local socioecological landscape, we have not demonstrated that these beliefs and appeals actually motivate corresponding behaviors that mitigate such threats. Even though particular religious systems exhibit clear features of adaptive self-organization (e.g., Bird et al, 2013;Lansing et al, 2017;Sosis and Bressler, 2003) and many other cases are interpreted as such (e.g., Angsongna et al, 2016;Connors, 2000;Leeson and Suarez, 2015;Rossano, 2007;Rappaport, 1968;Reynolds and Tanner, 1995;Strassmann et al, 2012), it remains unclear if appeals to deities actually motivate such systems (Purzycki and Sosis, 2022). 7 There is experimental evidence across 15 field sites showing that higher individual ratings of gods' general monitoring and punitive tendencies predict fairer and more generous behavior towards co-religionists in behavioral economic games (Lang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While the present work shows that appeals to gods and spirits point to threats to coordination and cooperation in the local socioecological landscape, we have not demonstrated that these beliefs and appeals actually motivate corresponding behaviors that mitigate such threats. Even though particular religious systems exhibit clear features of adaptive self-organization (e.g., Bird et al, 2013;Lansing et al, 2017;Sosis and Bressler, 2003) and many other cases are interpreted as such (e.g., Angsongna et al, 2016;Connors, 2000;Leeson and Suarez, 2015;Rossano, 2007;Rappaport, 1968;Reynolds and Tanner, 1995;Strassmann et al, 2012), it remains unclear if appeals to deities actually motivate such systems (Purzycki and Sosis, 2022). 7 There is experimental evidence across 15 field sites showing that higher individual ratings of gods' general monitoring and punitive tendencies predict fairer and more generous behavior towards co-religionists in behavioral economic games (Lang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While we have argued that the present work shows that appeals to gods and spirits reflect threats to coordination and cooperation in the local socioecological landscape, we have not demonstrated that these beliefs and appeals actually motivate corresponding behaviors that mitigate such threats. Even though particular religious systems exhibit clear features of adaptive self-organization (e.g., Bird et al, 2013;Lansing et al, 2017;Sosis and Bressler, 2003) and many other cases are interpreted as such (e.g., Angsongna et al, 2016;Connors, 2000;Leeson and Suarez, 2015;Rossano, 2007;Rappaport, 1968;Reynolds and Tanner, 1995;Strassmann et al, 2012), it remains unclear exactly how beliefs about and appeals to deities are implicated in such systems (Purzycki and Sosis, 2022). 7 There is experimental evidence across 15 diverse field sites showing that higher individual ratings of gods' general monitoring and punitive tendencies predict fairer and more generous behavior towards co-religionists in behavioral economic games (Lang et al, 2019).…”
Section: Implications and Cautionary Notesmentioning
confidence: 99%
“…While one must remain careful not to romanticize indigenous people's ways of life when evaluating such ethnographic reports (e.g., Alvard, 1994;Smith & Wishnie, 2000), the ethnographic record is brimming with similar instances of spiritually sanctioned conservation systems (e.g., Angsongna et al, 2016;Hartberg et al, 2016), at least hinting at causal implications to be tested in future research. For instance, a strikingly similar case to the Batak can be found in Atran et al's (2002) work among three neighboring rain-forest groups in the Maya lowlands of Guatemala.…”
Section: Forest Spirits Of the Batak And Itza' Mayamentioning
confidence: 99%